2019
DOI: 10.1038/s41467-019-11556-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD20 after viral reactivation renders HIV-reservoir cells susceptible to Rituximab

Abstract: The identification of exclusive markers to target HIV-reservoir cells will represent a significant advance in the search for therapies to cure HIV. Here, we identify the B lymphocyte antigen CD20 as a marker for HIV-infected cells in vitro and in vivo. The CD20 molecule is dimly expressed in a subpopulation of CD4-positive (CD4 + ) T lymphocytes from blood, with high levels of cell activation and heterogeneous memory phenotypes. In lymph node samples from infected patients, CD20 is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 47 publications
3
51
0
Order By: Relevance
“…Next, we applied PP-SLIDE to characterize latent cells from HIV-infected individuals, using a CyTOF panel ( Supplementary file 1 ) that is directed at markers of the major subsets and differentiation states of CD4+ T cells and includes receptors and intracellular proteins associated with latency ( Banga et al, 2016 ; Buzon et al, 2014 ; Chomont et al, 2009 ; Descours et al, 2017 ; Fromentin et al, 2016 ; Hogan et al, 2018 ; Iglesias-Ussel et al, 2013 ; Khoury et al, 2016 ; Li et al, 2019 ; Serra-Peinado et al, 2019 ; Sun et al, 2015 ). Since reactivation events are rare and reducing background was key, we conjugated different anti-Gag antibodies to three different metal lanthanides and only considered cells displaying a Gag signal in all three channels as true events.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we applied PP-SLIDE to characterize latent cells from HIV-infected individuals, using a CyTOF panel ( Supplementary file 1 ) that is directed at markers of the major subsets and differentiation states of CD4+ T cells and includes receptors and intracellular proteins associated with latency ( Banga et al, 2016 ; Buzon et al, 2014 ; Chomont et al, 2009 ; Descours et al, 2017 ; Fromentin et al, 2016 ; Hogan et al, 2018 ; Iglesias-Ussel et al, 2013 ; Khoury et al, 2016 ; Li et al, 2019 ; Serra-Peinado et al, 2019 ; Sun et al, 2015 ). Since reactivation events are rare and reducing background was key, we conjugated different anti-Gag antibodies to three different metal lanthanides and only considered cells displaying a Gag signal in all three channels as true events.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Serra-Peinado et al reported a higher percentage of HIV RNA + cells among cells expressing CD20 (96). CD20 is a known B-cell surface marker but is dimly expressed on a small subpopulation of CD4 + T cells.…”
Section: Cd2 Cd30 and Cd20mentioning
confidence: 99%
“…CD20 is a known B-cell surface marker but is dimly expressed on a small subpopulation of CD4 + T cells. Although the contribution of CD20 dim CD4 + T cells to the total pool of HIV RNA + cells was modest (median of 18.6% in ART-treated and 25.0% in viremic HIV-infected individuals), ex vivo treatment of primary peripheral blood mononuclear cells (PBMCs) from ART-suppressed individuals with the anti-CD20 monoclonal antibody Rituximab appeared to reduce the pool of HIV RNA + cells when combined with latency-reversing agents (96). Further studies are needed to elucidate whether Rituximab treatment is also capable of reducing the total or intact HIV DNA reservoir.…”
Section: Cd2 Cd30 and Cd20mentioning
confidence: 99%
“…These factors include the immune negative checkpoints PD-1, TIGIT, LAG-3 ( Fromentin et al, 2016 ), and CTLA-4 ( McGary et al, 2017 ), as well as other factors such as CD2 ( Iglesias-Ussel et al, 2013 ), CCR6 ( Gosselin et al, 2017 ), and Survivin ( Kuo et al, 2018 ). Other host factors are shown to be enriched, in particular, in HIV-infected transcriptionally active cells, such as CD30 ( Hogan et al, 2018 ) and CD20 ( Serra-Peinado et al, 2019 ). These factors, especially those that reside on the cell surface, may be useful for targeting these cells and can provide a better understanding of HIV persistence biology.…”
Section: Discussionmentioning
confidence: 99%